(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The modern global economy is becoming more digital, and at great speed, intensity, and scale. Its international universal ‘language’ is information technology. Only this ‘language’ is objectively possible to ‘understand’, to interact concerning isolated, national reproductions taking place in many states. It is the need for this understanding, as well as for its practical use, that act as the criteria reasons for digitalization of the national economy of Russia as a whole, and its organic component - the agro-industrial complex. Another reason, is the economic necessity of the above-mentioned phenomenon, which allows receiving, store and transmit information about counterparties, tariffs and make contracts, make fuller use of limited resources, and in the best way satisfy both production and personal needs of various subjects in real-time [1]. The article reveals the content of the modern stage of the Russian agro-industrial complex digitalization in its integrity and specificity